Visualization and interaction of finite element analysis in augmented reality. (March 2017) - Huang, J.M.; Ong, S.K.; Nee, A.Y.C.
Abstract: In this paper, augmented reality (AR) is used to enhance the visualization and interaction of finite element analysis (FEA) of structures. An integrated simulation system is proposed which acquires input data using sensors and uses AR technology to visualize FEA results in the real world. A number of intuitive interaction methods have been devised and implemented in this system. The user can perform real-time FEA simulation to investigate structural behavior under different loading conditions either through manipulating virtual loads or creating different loading conditions. Exploration of FEA results is enhanced through natural interfaces for manipulating, slicing and clipping the result data. Moreover, the user can modify the FE models of the structures through simplified operations for different purposes, e.g., adding structural members for stiffening and performing local mesh refinement. The modified model can be re-analyzed automatically. A prototype system has been built and a case study has been implemented to demonstrate the innovative interaction methods and evaluate the system performance. Highlights: Investigation of structural behavior by using real-time FEA in AR. Intuitive data exploration through slicing, clipping and manipulating FEA results. AR-assisted interactive analysis with model modification.